Cultural Translation and Postcolonial Poetry - Bery, A. author. aut Link
VIII, 221 p.
Keywords: This book uses the framework of cultural translation to explore the work of six significant modern writers from Ireland, India, Australia and the Caribbean. Written in an accessible and approachable style, it will be of interest not only to specialists in postcolonial literatures, but also readers of modern and contemporary poetry more generally.